Radiation-resistant, high-temperature-resistant and high-emissivity protective coating as well as preparation method and application thereof

By using acrylic modified silicone resin, specific fillers and modified nanomaterials in the coating, a multiple protection mechanism is formed, which solves the problem of cracking and peeling of the coating in high radiation and high temperature environments, and achieves effective protection and improved heat dissipation performance in nuclear reactors.

CN120795793APending Publication Date: 2025-10-17NORTHEASTERN UNIV CHINA +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511132566.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-24
Filing Date
2025-08-13
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing coatings are prone to cracking and falling off under high radiation and high temperature environments, and cannot effectively protect devices. In addition, traditional organic coatings are difficult to use in the high temperature environment inside a nuclear reactor.

Method used

Adopting acrylic modified silicone resin as the matrix, combined with specific fillers and enamel, adding nano silicon carbide particles modified by silane coupling agent, modified double hydroxide nanosheets and boron nitride whiskers to form a multiple protection mechanism, enhancing the radiation resistance, high temperature resistance and high emissivity performance of the coating.

Benefits of technology

The coating does not powder or peel off in high radiation and high temperature environments, which significantly improves the service life of the device, adapts to the high temperature and high pressure environment within the nuclear reactor, and has excellent heat dissipation performance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005547156210000011
    Figure HDA0005547156210000011
  • Figure HDA0005547156210000012
    Figure HDA0005547156210000012
Patent Text Reader

Abstract

The invention provides a radiation-resistant, high-temperature-resistant and high-emissivity protective coating as well as a preparation method and application thereof, and belongs to the technical field of material engineering. Comprising 20-30 parts of acrylic acid modified organic silicon resin, 15-20 parts of polyurethane resin, pigment and filler and 2-11 parts of enamel. The pigment filler is prepared from 1 to 3 parts of Ta, 1 to 3 parts of V, 5 to 8 parts of copper chrome black, 5 to 7.5 parts of iron manganese black, 10 to 13 parts of B4C and 1 to 3 parts of Ta2O5; the preparation method comprises the following steps: ball-milling and mixing the acrylic modified organic silicon resin, the pigment filler, the enamel and the diluent, uniformly mixing, adding the polyurethane resin, and uniformly dispersing to obtain the coating. The protective coating prepared by the invention has an excellent protective effect in nuclear radiation and high-temperature environments, and can effectively resist nuclear radiation and improve the heat dissipation rate, so that the surface temperature of a device is reduced, the surface temperature of the device is not increased, and the device is effectively protected.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of material engineering, and particularly relates to a radiation-resistant, high-temperature-resistant and high-emissivity protective coating and a preparation method thereof. BACKGROUND

[0002] In some special environments, such as space, nuclear radiation areas or high-temperature and high-radiation environments, devices operating in the environment are prone to damage due to long-term exposure to strong radiation and high temperature. Therefore, in order to protect these devices, a coating is often applied to the surface of the device to reduce the influence of strong radiation and high temperature.

[0003] However, since the coating protects the device, it is also in a high-radiation and high-temperature environment. If the coating itself has limited high-temperature resistance or radiation resistance, its surface is prone to cracking and falling off during long-term use, which makes it difficult to effectively protect the internal device. SUMMARY

[0004] The present application aims to provide a radiation-resistant, high-temperature-resistant and high-emissivity protective coating and a preparation method and application thereof, which can effectively isolate nuclear radiation and reduce the surface temperature of the device, thereby reducing the influence of high radiation and high temperature on the device and effectively improving the service life of the device.

[0005] The present application is achieved by the following technical solutions: A radiation-resistant, high-temperature-resistant and high-emissivity protective coating comprises the following components by weight: 20-30 parts of acrylic modified silicone resin, 15-20 parts of polyurethane resin, color filler and 2-11 parts of enamel; The color filler comprises 1-3 parts of Ta, 1-3 parts of V, 5-8 parts of copper-chromium black, 5-7.5 parts of iron-manganese black, 10-13 parts of B4C and 1-3 parts of Ta2O5.

[0006] As some embodiments of the present application, the protective coating comprises the following components by weight: 22-28 parts of acrylic modified silicone resin, 16-19 parts of polyurethane resin, color filler and 6-10 parts of enamel; The color filler comprises 1.2-2.5 parts of Ta, 1.2-2.5 parts of V, 5.5-7.5 parts of copper-chromium black, 5.5-7 parts of iron-manganese black, 10.5-12 parts of B4C and 1.5-2.8 parts of Ta2O5.

[0007] As some embodiments of the present application, the protective coating comprises the following components by weight: 26 parts of acrylic modified silicone resin, 18 parts of polyurethane resin, color filler and 10 parts of enamel; The pigment filler includes 2.2 parts of Ta, 2 parts of V, 6 parts of copper-chromium black, 6 parts of iron-manganese black, 12 parts of B4C, and 2 parts of Ta2O5.

[0008] As some embodiments of the present application, the protective coating further includes glass powders with different melting points.

[0009] As some embodiments of the present application, the glass powders include SiO2-B2O3-Al2O3-CaF2-R2O (R is Na or K), SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2, and SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2.

[0010] As some embodiments of the present application, the coating further includes 0.3-1.2 parts of nano-silicon carbide particles modified by a silane coupling agent, 0.5-2 parts of modified double-hydroxide nanosheets, and 0.2-0.8 parts of boron nitride whiskers modified by a silane coupling agent. The modified double-hydroxide nanosheets are obtained by modifying a magnesium-aluminum-based double-hydroxide by a silane coupling agent, and the magnesium-aluminum-based double-hydroxide is doped with Ce 3+ or La 3+ .

[0011] As some embodiments of the present application, the doping amount of Ce 3+ or La 3+ in the magnesium-aluminum-based double-hydroxide is 5-10 mol%.

[0012] As some embodiments of the present application, the protective coating further includes one or more of a defoaming agent, a leveling agent, and a dispersing agent.

[0013] As some embodiments of the present application, the coating has a coating thickness of 50-120 μm.

[0014] In addition, to achieve the above-mentioned purpose, the present application further provides a preparation method of a radiation-resistant, high-temperature-resistant, and high-emissivity protective coating. The acrylic-modified silicone resin, the pigment filler, the enamel, and the diluent are ball-milled and mixed, and after being uniformly mixed, the polyurethane resin is added, and the coating is prepared after being uniformly dispersed.

[0015] In addition, to achieve the above-mentioned purpose, the present application further provides an application of the radiation-resistant, high-temperature-resistant, and high-emissivity protective coating in a primary loop. The primary loop includes a nuclear reactor pressure vessel, a main pump, a steam generator, a pressurizer, and pipelines connecting these devices.

[0016] Compared with the prior art, the present application has the following beneficial effects: 1. The present application adopts acrylic modified silicone resin as the matrix, adds special fillers and enamel, and obtains protective coating with radiation resistance, high temperature resistance and high emissivity. The coating has excellent protective effect under nuclear radiation and high temperature environment, can effectively resist nuclear radiation, improve the heat dissipation rate, and then reduce the device surface temperature, so that the device surface does not heat up, effectively protects the device, and can be widely applied to the outer surface of aerospace / spacecraft, 3-4 generation advanced sodium-cooled reactor equipment or certain type of hot end component surface.

[0017] Specifically, the performance indicators of the protective coating in the present application are as follows: The protective coating has a radiation resistance of 1.7*10 5 The coating does not powder and peel off under a radiation dose of 1.7*10 The protective coating realizes temperature resistance of 1000-200 hours at high temperature of 600-700℃, which refers to superhigh temperature accelerated oxidation behavior; if it is actually used in devices, it can be used for more than 3 months to 1 year; After the protective coating is coated, the surface temperature of the coated sample is reduced by about 10% at high temperature of 600-700℃; the emissivity is greater than or equal to 0.90 at 50℃ and greater than or equal to 0.85 at 650℃ in the 9-12μm frequency band.

[0018] 2. By introducing components such as silane coupling agent modified nano silicon carbide particles, modified LDH nanosheets and silane coupling agent modified BN whiskers into the coating, the components can play a synergistic effect with the original components, significantly improve the high-pressure cracking resistance, steam barrier property and corrosion-resistant ion capacity of the coating, effectively adapt to the harsh environment of 300-400℃, 10-15MPa and γ ray radiation in the primary circuit, and realize more comprehensive protection effect. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 : Surface and cross-sectional morphology of the coating in Example 3 in the prepared state; wherein, Figure 1 (a) is a surface morphology diagram of the coating in the prepared state; Figure 1 (b) is a cross-sectional morphology diagram of the coating; Figure 2 : Surface and cross-sectional morphology of the coating in Example 3 after high temperature oxidation at 650℃ for 1500h; wherein, Figure 2 (a) is a surface morphology diagram of the coating in the prepared state; Figure 2 (b) is a cross-sectional morphology diagram of the coating. DETAILED DESCRIPTION

[0020] In the prior art, the paint used in some special environments, such as space, nuclear radiation area or high temperature and high radiation environment, is prone to cause the surface of the coating to crack and fall off due to long time in high radiation and high temperature environment, thereby causing the internal device to be difficult to be effectively protected.

[0021] Based on this, the present application provides a kind of radiation resistance, high temperature resistance and high emissivity protective coating, comprising the following components by weight: 20-30 parts of acrylic modified silicone resin, 15-20 parts of polyurethane resin, pigment and filler and 2~11 parts of enamel; The pigment and filler include 1-3 parts of Ta, 1-3 parts of V, 5-8 parts of copper chromium black, 5-7.5 parts of iron manganese black, 10-13 parts of B4C and 1-3 parts of Ta2O5.

[0022] In the above scheme, the acrylic modified silicone resin is used as the matrix of the protective coating, which has excellent heat resistance, weather resistance, acid and alkali resistance, corrosion resistance and strong adhesion; on the basis of the matrix, the filler and enamel are added to form a special nuclear radiation resistance skeleton in the protective coating, which shows excellent stability in the nuclear radiation environment, and improves the heat dissipation rate, so that the surface temperature / emissivity index does not decrease for a long time; specifically, the oxides such as copper chromium black and iron manganese black have good high temperature stability and high emissivity; boron carbide has the characteristics of low density, high strength, good high temperature stability and chemical stability, can absorb a large amount of neutrons without forming any radioactive isotope, so it is an ideal neutron absorber in nuclear power plants; the enamel can fill the pores in the coating and improve the compactness of the coating, thereby improving the protective performance of the coating.

[0023] The present application creates a double protection mechanism by integrating the nuclear radiation resistance components and high emissivity fillers, so that the coating can meet the requirements of nuclear radiation and high temperature heat dissipation at the same time.

[0024] It is worth noting that the emissivity of a general coating can meet the higher requirements at the initial stage or after not being subjected to extreme environment, but once it is used at high temperature, the emissivity will decrease rapidly. The present application can make the coating have good high temperature thermal stability by limiting the components of the filler, and on the other hand, even after the initial or process decomposition, it can still react quickly and produce in situ, so as to play a protective role for a long time.

[0025] Through the synergistic effect of the above components, the prepared protective coating can effectively isolate nuclear radiation and reduce the surface temperature of the device, thereby protecting the device.

[0026] Specifically, the performance indicators of the protective coating in the present application are as follows: The protective coating has a surface temperature of 1.7×10 5Under the irradiation dose of Gy above (the nuclear irradiation test of the present application is completed at 350 DEG C), the coating is not pulverized and peeled off; The protective coating realizes temperature resistance of 1000- (200) hours above at high temperature 600- (700 DEG C), which refers to super-high temperature accelerated oxidation behavior; if it is actually used in a device, it can reach 3 months to 1 year above; It is worth mentioning that the conventional organic coating is very difficult to break through the temperature limit, and the general use temperature is about 120 DEG C, while the general temperature in a nuclear reactor is about 120 DEG C, that is, the conventional organic coating can barely be applied, but in a primary loop, the general temperature is 300-400 DEG C, and the conventional coating is difficult to be applied at this temperature. The use temperature of the organic silicon coating developed in the present application can be increased to 600-700 DEG C, which is extremely difficult, and the high temperature environment can be applied to some high temperature hot end parts in the nuclear environment, such as heat exchangers and some heat transfer pipelines.

[0027] After the protective coating is coated, the surface temperature of the coated sample is reduced by about 10% at 600-700 DEG C high temperature; the emissivity is greater than or equal to 0.90 at 50 DEG C in the 9-12 mu m band; the emissivity is greater than or equal to 0.85 at 650 DEG C.

[0028] In order to further improve the protection effect of the protective coating, as some embodiments of the present application, the amount of the protective coating is further limited, that is, the protective coating comprises the following components by weight: 22-28 parts of acrylic modified silicone resin, 16-19 parts of polyurethane resin, pigment and filler, and 6-10 parts of enamel; The pigment and filler comprises 1.2-2.5 parts of Ta, 1.2-2.5 parts of V, 5.5-7.5 parts of copper chromium black, 5.5-7 parts of iron manganese black, 10.5-12 parts of B4C and 1.5-2.8 parts of Ta2O5.

[0029] In order to further improve the protection effect of the protective coating, as some embodiments of the present application, the amount of the protective coating is further limited, that is, the protective coating comprises the following components by weight: 26 parts of acrylic modified silicone resin, 18 parts of polyurethane resin, pigment and filler, and 10 parts of enamel; The pigment and filler comprises 2.2 parts of Ta, 2 parts of V, 6 parts of copper chromium black, 6 parts of iron manganese black, 12 parts of B4C and 2 parts of Ta2O5.

[0030] In order to further improve the protection effect of the protective coating, as some embodiments of the present application, the components of the enamel are further limited, that is, the enamel comprises a plurality of glass powders with different melting points.

[0031] In the scheme, the glass powder in the coating can adjust the thermal expansion of the coating on the one hand, and can be used as a secondary binder to repair cracks, holes and other defects caused by pyrolysis of organic resins at high temperature; and in order to adapt to the use environment of the coating at different temperatures, glass powder with different melting points needs to be selected for adaptation.

[0032] In order to further improve the protection effect of the protective coating, as some embodiments of the present application, the components of the enamel are further limited, that is, the glass powder comprises SiO2-B2O3-Al2O3-CaF2-R2O (R is Na or K), SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2 and SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2.

[0033] In order to further improve the adhesion and density of the coating prepared by the protective coating, as some embodiments of the present application, the components of the protective coating are further limited, that is, the protective coating further comprises one or more of defoaming agent, leveling agent and dispersant, wherein the defoaming agent, leveling agent or dispersant is 0.1-0.3 parts.

[0034] In order to further improve the protection effect of the protective coating, as some embodiments of the present application, the thickness of the coating is further limited, that is, the coating thickness of the coating is 50~120μm. If the coating thickness is too small, the radiation resistance, corrosion resistance, high temperature resistance and emissivity will be weakened, and if the coating thickness is too thick, it is easy to crack and peel off, which affects the protection effect.

[0035] The present application prepares the coating by uniformly ball-milling acrylic modified silicone resin, pigment and filler, and then fully mixing with polyurethane resin, which has the advantages of simple preparation method, fast speed and low cost.

[0036] Based on the environmental characteristics of the primary loop, the present application also provides the application of the radiation-resistant, high-temperature-resistant and high-emissivity protective coating in the primary loop, wherein the primary loop comprises a nuclear reactor pressure vessel, a main pump, a steam generator, a pressure stabilizer and a pipeline connecting the devices.

[0037] The above-mentioned coating (i.e. the original coating) has strong radiation resistance, high temperature resistance and high emissivity, can effectively cope with the challenges brought by high temperature conduction and radiation, can reliably protect the outer surface of aerospace / spacecraft, the surface of equipment in 3-4 generation advanced sodium-cooled reactor and certain type of hot end components, and its temperature resistance and radiation resistance can adapt to the high temperature environment and nuclear radiation environment of the primary loop at 300-400℃.

[0038] However, the service conditions of a primary circuit are far more complex than simply high temperature or radiation. For example, while the outer surface of the primary circuit piping does not directly contact the internal high-temperature, high-pressure water / steam, it is exposed to the complex and harsh environment of the entire system for a long time, facing two core challenges: Although the outer surface of the primary-loop pipeline is not in direct contact with the internal high-temperature and high-pressure water / steam, it is exposed to the harsh environment of the entire system for a long time: the high pressure of 10-15MPa inside the pipeline will cause the pipeline to undergo slight expansion deformation. After this deformation is transmitted to the outer coating, it will cause continuous stress concentration inside the coating. The mechanical strength of the original coating is not sufficient to withstand this long-term stress, and it is prone to cracks, which will destroy the protection integrity. At the same time, when the primary-loop system is in operation, the outer surface of the pipeline may form condensed steam due to the temperature difference with the surrounding environment, or a small amount of steam may be diffused due to minor leaks in the system. The permeability of these steam is enhanced at high temperatures and can penetrate through the microscopic pores that may exist in the original coating, resulting in a decrease in the interfacial bonding strength between the coating and the pipeline substrate, causing peeling. The density and anti-permeation properties of the original coating cannot completely block such penetration.

[0039] Based on this, although the above coating can adapt to the high temperature and nuclear environment of the primary circuit, it is difficult to effectively adapt to the harsh environment of the primary circuit pipeline. Based on this, on the basis of the above coating, it also includes 0.3-1.2 parts of nano-silicon carbide particles modified by a silane coupling agent (such as KH-792), 0.5-2 parts of modified double hydroxide (LDH) nanosheets, and 0.2-0.8 parts of boron nitride (BN) whiskers modified by a silane coupling agent (such as KH-792); the modified double hydroxide nanosheets are obtained by modifying magnesium aluminum double hydroxide with a silane coupling agent (such as KH-792), and the magnesium aluminum double hydroxide is doped with Ce. 3+ or La 3+ .

[0040] By adding these new components to the original coating, the new coating can be effectively adapted to the primary circuit environment, allowing it to be used to protect the surfaces of metal components in the primary circuit under conditions of 300-400°C, 10-15 MPa, and gamma ray radiation. The specific functions of the new components are as follows: Nano-SiC particles modified with a silane coupling agent: Nano-SiC has high hardness and excellent compressive strength, which can directly resist the stress concentration transmitted to the outer coating by pipeline deformation under high pressure of 10-15MPa, reducing crack initiation and adapting to high-pressure environments. Modification with the silane coupling agent KH-792 improves its compatibility with the original coating resin matrix (such as acrylic modified silicone resin), avoiding local defects caused by agglomeration, ensuring uniform mechanical properties of the coating, and adapting to the structural stability requirements under high temperatures.

[0041] Modified double hydroxide (LDH) nanosheet: after modification by silane coupling agent KH-792, the layered structure of the magnesium-aluminum-based LDH can form a physical barrier, effectively blocking the penetration of steam and condensed water at a high temperature of 300-400°C, and adapting to the risk of environmental steam permeation; the doped Ce 3+ or La 3+ can stabilize the crystal structure of the LDH, increase the thermal decomposition temperature of the LDH to above 650°C, resist high temperatures in the primary loop, and avoid structural collapse at high temperatures; at the same time, the ion exchange performance of the LDH can adsorb trace corrosive ions (such as Cl — ) in the steam, reduce the swelling risk of the coating, and adapt to corrosive environments.

[0042] Boron nitride whisker modified by a silane coupling agent: BN whiskers have a fibrous structure, can disperse local stress at high pressure, inhibit crack propagation, and synergistically enhance the anti-cracking ability of the coating with nano-SiC, adapting to high-pressure environments; the BN whisker itself can resist temperatures >900°C, and after modification by the silane coupling agent KH-792, the bonding force with the resin is enhanced, and the structure can still remain stable at a high temperature of 300-400°C, adapting to high-temperature environments; at the same time, the chemical inertness makes it not affected by γ-ray radiation, adapting to radiation environments.

[0043] In addition, the newly added components can also form a complementary function with the resin, pigments and fillers (Ta, V, B4C, etc.), and glass powder in the original coating: First, the modified nano-SiC and BN whiskers enhance the interfacial bonding with the resin, combine the high-temperature resistance of the resin with the mechanical strengthening of the new components, form a “high-temperature-resistant - high-strength” composite matrix, and improve the overall structural stability.

[0044] Second, the glass powder in the original coating can fill small cracks through high-temperature melting, form a “prevention - repair” dual mechanism with the anti-cracking effect of nano-SiC, and strengthen the structural integrity at high pressure; the densification effect of the enamel and the blocking effect of the LDH nanosheet are superimposed to form multiple barriers, further blocking the penetration of steam.

[0045] In summary, the new components solve the problems of high-pressure stress, high-temperature stability, and steam permeation in a targeted manner, and synergistically realize the overall performance improvement of “radiation resistance - high-temperature resistance - high-pressure resistance - anti-permeation” with the original components, and fully adapt to the primary loop environment.

[0046] As some embodiments of the present application, in the magnesium-aluminum-based double hydroxide, Ce 3+ or La 3+The doping amount of the rare earth ions is 5-10 mol%. If the doping amount is too low, the rare earth ions are difficult to fully fill the lattice defects, and the stabilizing effect on the crystal structure of the LDH is limited, and the layered structure is still prone to collapse at high temperature. If the doping amount is too high, the excess Ce 3+ or La 3+ will cause lattice distortion, which will damage the integrity of the layered structure of the LDH, reduce the barrier ability to steam and ion exchange performance, and cannot adapt to the high temperature environment requirement of the primary loop at 300-400℃.

[0047] In addition, when the primary loop system is running, the outer surface of the pipeline will contact various corrosive species: first, the condensate on the surface of the pipeline may mix with trace corrosive media leaked from the system; second, if there are defects in the coating, local corrosion of the metal substrate of the pipeline will produce Fe 3+ , Ni 2+ and other ions. These corrosive species will adhere to the surface of the outer coating and try to penetrate. The existing coating for the primary loop can mainly play an adsorption role against C — , but the adsorption capacity of Fe 3+ , Ni 2+ and other corrosive species is limited, and long-term accumulation may cause the accumulation of corrosive media inside the coating, leading to local swelling. Based on this, the magnesium-aluminum-based LDH is further modified between the layers, and 0.3-0.8 parts of EDTA disodium derivative is introduced to enhance the adsorption capacity of Fe 3+ , Ni 2+ and other metal ions through coordination, and synergize with the original Cl — adsorption function to comprehensively resist the erosion of complex corrosive species in the primary loop water.

[0048] The preparation of the protective coating described in the application will be further described in detail in conjunction with the specific implementation modes.

[0049] Among them, the raw materials not mentioned in the examples and comparative examples and the preparation method are commercially available products.

[0050] Example 1 28 parts of acrylic modified silicone resin, 1.8 parts of Ta, 3 parts of V, 5 parts of copper chromium black, 6 parts of iron manganese black, 10 parts of B4C and 1.5 parts of Ta2O5, 7.5 parts of glass powder (consisting of 2 parts of SiO2-B2O3-Al2O3-CaF2-Na2O, 3.5 parts of SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2, 2 parts of SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2), 8 parts of enamel (selected from the enamel powder in Example 1 in the patent with application number CN201810069695.7), 11 parts of diluent (xylene), 0.1 parts of leveling agent (BYK-354), 0.2 parts of defoaming agent (BYK-052) and 0.2 parts of wetting agent (Dow Chemical BD-405) are ball milled and mixed, after being uniformly mixed, 20 parts of polyurethane resin is added, and dispersed at a speed of 1500-2500 rpm for 20-40 min to prepare the coating.

[0051] The coating is applied on the surface of 304 stainless steel subjected to surface sand blasting by spraying, brushing or dipping, and after curing at 120℃, a protective coating of 80μm is prepared. No crack is found in the protective coating by electron microscope observation, and the density is >90%.

[0052] The specific performance of the protective coating is as follows: After 1.7×10 5 Gy of γ-ray radiation, only the surface of the coating is oxidized and discolored, the coating is intact, and no powdering and peeling phenomenon occurs; After 1000 h of high temperature resistance at 600℃, no powdering and peeling phenomenon occurs in the coating; after 200 h of high temperature resistance at 700℃, no powdering and peeling phenomenon occurs in the coating; At 650℃ high temperature, the surface temperature of the substrate decreases by 6.5±1℃; in the frequency band of 9-12μm, the emissivity at 50℃ is ≥0.90; the emissivity at 650℃ is ≥0.85; Mechanical strength: the adhesion strength is 9.8 Mpa, the impact strength is 30 cm, and the flexibility is 2 rank.

[0053] In addition, the "radiation-high temperature coupling environment" test environment is also used: first, 1.7×10 5 Gy of γ-ray radiation (simulating a primary loop nuclear radiation environment) is applied at 350℃, and then immediately placed in a 650℃ high temperature environment for aging (simulating high temperature service), and the change of the emissivity of the coating is monitored in real time during the period. The results are as follows: Radiation resistance and high temperature resistance: after 1.7×10 5After 100 Gy radiation, there is no powdering on the coating surface; after being exposed to a high temperature of 650℃ for 900 hours, the coating is still intact without any powdering or peeling. Emissivity: 650℃ (after radiation + high temperature 900h) emissivity ≥ 0.85. Example 2 25 parts of acrylic modified silicone resin, 2 parts of Ta, 1.8 parts of V, 5.5 parts of copper chrome black, 6 parts of iron manganese black, 10.5 parts of B4C and 2 parts of Ta2O5, 8.5 parts of glass powder (composed of 2.5 parts of SiO2–B2O3–Al2O3–CaF2-Na2O, 2.5 parts of SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2, 3.5 parts of SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6 SrO2 composition), 8.5 parts of enamel (selected from the enamel powder in Example 1 of the patent application number CN201810069695.7), 10 parts of diluent (xylene), 0.1 parts of leveling agent (BYK-354), 0.2 parts of defoaming agent (BYK-052) and 0.2 parts of wetting agent (Dow Chemical BD-405) are ball-milled and mixed. After the mixture is evenly mixed, 18 parts of polyurethane resin are added and evenly dispersed to obtain the coating.

[0054] The coating is sprayed, brushed or dipped onto a 304 stainless steel surface that has been sandblasted, and cured at 120° C. to obtain an 80 μm protective coating. Electron microscopic observation of the protective coating shows no cracks, and the density is greater than 90%.

[0055] The specific properties of the protective coating are as follows: 1.7×10 5 After irradiation with γ-rays of 1000 Gy, only the surface of the coating was oxidized and discolored, and the coating was intact without any powdering or peeling. The coating showed no powdering or peeling after continuous high temperature resistance at 600℃ for 1200h; and no powdering or peeling after continuous high temperature resistance at 700℃ for 230h. At a high temperature of 650℃, the substrate surface temperature drops by 6.7±1℃; in the 9~12μm frequency band, the emissivity at 50℃ is ≥0.90; at 650℃, the emissivity is ≥0.85; Mechanical strength: Adhesion strength is 10.05Mpa, impact strength is 33 cm, and flexibility is 2 rank.

[0056] In addition, the “radiation-high temperature coupling environment” test environment was used: first, 1.7×10 5Gy of gamma ray radiation, and then immediately placed in a high temperature environment of 650℃ for continuous aging (simulating high temperature service), during which the emissivity change of the coating was monitored in real time, and the results are as follows: Radiation resistance and high temperature resistance: after 1.7×10 5 After 1.7×10 Emissivity: 650℃ (after radiation + high temperature for 1000h) emissivity ≥0.85.

[0057] Example 3 The 26 parts of acrylic modified silicone resin, 2.2 parts of Ta, 2 parts of V, 6 parts of copper chromium black, 6 parts of iron manganese black, 12 parts of B4C and 2 parts of Ta2O5, 10 parts of glass powder (composed of 3.5 parts of SiO2-B2O3-Al2O3-CaF2-Na2O, 3.5 parts of SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2, 3 parts of SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2), 10 parts of enamel (selected from the enamel micro powder in Example 1 in the patent with the application number CN201810069695.7), 11.5 parts of diluent (xylene), 0.1 parts of leveling agent (BYK-354), 0.2 parts of defoaming agent (BYK-052) and 0.2 parts of wetting agent (Dow Chemical BD-405) are ball milled and mixed, and after being uniformly mixed, 18 parts of polyurethane resin is added and uniformly dispersed to prepare the coating.

[0058] The coating is sprayed, brushed or dipped on the surface of the 304 stainless steel after surface sand blasting treatment, and after curing at 120℃, a 80μm protective coating is prepared, and the surface and cross-sectional morphology of the protective coating is observed by electron microscopy as shown in Figure 1 , and no cracks are found, and the density is >90%.

[0059] The specific properties of the protective coating are as follows: After 1.7×10 5 After 1.7×10 Gy of gamma ray radiation, and then immediately placed in a high temperature environment of 650℃ for continuous aging (simulating high temperature service), during which the emissivity change of the coating was monitored in real time, and the results are as follows: Figure 2 Figure 1 and Figure 2 , the dark gray is the resin, some light gray is the non-metallic filler and enamel, and the white bright is the metal filler), and no peeling and spalling phenomenon occurs to the coating; at 700℃ for continuous high temperature resistance for 300h, no peeling and spalling phenomenon occurs to the coating; according to Figure 1 ​(a) It can be seen that the original coating surface is dense, the filler is uniformly dispersed, and there is no defect such as microcrack; by Figure 2 (a) It can be seen that the coating surface is smooth after high-temperature oxidation, and no cracks or holes are found. Figure 1 (b) and Figure 2 The cross-sectional morphology of (b) shows that the coating is well combined with the substrate, there is no obvious oxidation layer between the substrate and the coating, and the substrate is well protected.

[0060] At a high temperature of 650℃, the surface temperature of the substrate decreases by 7±1.2℃; in the 9~12μm frequency band, the emissivity is ≥0.90 at 50℃; the emissivity is ≥0.85 at 650℃; Mechanical strength: the adhesion strength is 9.76 Mpa, the impact strength is 29 cm, and the flexibility is 2 rank.

[0061] In addition, the "radiation-high temperature coupling environment" test environment is also used: first, 1.7×10 5 Gy of γ-ray radiation is applied at 350℃, and then immediately placed in a 650℃ high-temperature environment for continuous aging, during which the change of the emissivity of the coating is monitored in real time, and the results are as follows: Radiation resistance and high-temperature resistance: after 1.7×10 5 Gy of radiation, the coating is intact; after 1050h at 650℃ high temperature, the coating is still free of powdering and peeling. Emissivity: the emissivity at 650℃ (after radiation + high temperature for 1050h) is ≥0.85.

[0062] From the performance of the above Examples 1-3, it can be seen that the protective coating prepared in the present application has excellent radiation resistance, high-temperature resistance, and emissivity, and also has strong adhesion strength and impact strength, etc.

[0063] Among them, in Examples 1-3, the emissivity at 650℃ under the coupling environment is still ≥0.85, which is consistent with the emissivity at 650℃ alone, indicating that the radiation does not significantly damage the emissivity characteristics of copper chromium black and iron manganese black, and the repairing effect of the glass powder at high temperature effectively maintains the denseness of the coating, ensuring the stability of the emissivity.

[0064] Example 4 On the basis of Example 1, additionally adding: 0.8 parts of nano-SiC particles modified by KH-792 (particle size 100nm), 1.2 parts of modified LDH nanosheets, and 0.5 parts of BN whiskers modified by KH-792; the rest of the components and the amount are the same as in Example 1. The preparation method of the new components is as follows: Preparation of the KH-792 modified nano-SiC particles: take 100 parts of nano-SiC particles, add 5 parts of silane coupling agent KH-792 and appropriate amount of anhydrous ethanol, ultrasonic dispersion (power 400W, time 45min), then stir and react at 80℃ for 2h, and dry at 60℃ under vacuum until constant weight. Preparation of the modified LDH nanosheets: ①According to the molar ratio of Mg 2+ : Al 3+ : Ce 3+ = 3:0.8:0.2, weigh magnesium nitrate, aluminum nitrate and cerium nitrate, and dissolve them in deionized water to prepare a metal salt solution (the total ionic substance concentration of the metal is 0.25mol / L); according to the molar ratio of OH — : CO3 2— = 5:1, weigh sodium hydroxide and sodium carbonate, and dissolve them in deionized water to prepare an alkali solution (the total substance concentration of sodium hydroxide and sodium carbonate is 0.25mol / L); mix the two solutions according to the volume ratio of 1:1 and co-precipitate at 60℃, stir and react for 1h, then hydrothermally react at 100℃ for 6h, centrifugal wash until neutral, dry to obtain a magnesium-aluminum-based LDH; ②Take 100 parts of the magnesium-aluminum-based LDH, add 6 parts of KH-792 and appropriate amount of isopropanol, stir and react at 60℃ for 3h, and dry at 60℃ under vacuum until constant weight. Preparation of the KH-792 modified BN whiskers: take 100 parts of BN whiskers, add 4 parts of KH-792 and appropriate amount of acetone, high-speed stirring (2500rpm, 30min), and dry at 85℃ until constant weight. Example 5 On the basis of Example 4, only adjust the amount of newly added in Example 4, after adjustment: 0.5 parts of KH-792 modified nano-SiC particles (particle size 100nm), 1.8 parts of modified LDH nanosheets, 0.3 parts of KH-792 modified BN whiskers; the rest of the components and the amount, and the preparation method are the same as Example 4.

[0065] Example 6 Compared with Example 4, interlayer modification of the modified LDH nanosheets: additionally introduce 0.5 parts of calcium disodium ethylenediaminetetraacetate; the rest of the components and the amount are the same as Example 4. Among them, the preparation of the interlayer modified LDH nanosheets: in the second step of the preparation of the modified LDH nanosheets in Example 4, add 0.5 parts of EDTA disodium derivative, stir and react at 70℃ for 1.5h, and dry under vacuum until constant weight to obtain the interlayer modified LDH nanosheets. The coating prepared in Example 4-6 was used to prepare a 80 μm thick coating on a sample panel according to the spraying method in Example 1, and then the sample panel was tested for radiation resistance and high temperature resistance and emissivity according to the "radiation-high temperature coupling environment" test method (same as in Example 1), and the results were as follows: Radiation resistance and high temperature resistance: after 1.7 x 10 5 After 1.7 x 10 Emissivity: 650℃ emissivity ≥ 0.85. Comparative Example 1 Comparing with Example 3, only the enamel and glass powder were removed, and the other parameters were the same as in Example 3.

[0066] The coating was sprayed, brushed or dipped on the surface of a 304 stainless steel surface which was subjected to surface sand blasting, and after curing at 120℃, a 80 μm protective coating was prepared.

[0067] The specific properties of the protective coating were as follows: After 1.7 x 10 5 After 1.7 x 10 After 600℃ high temperature for 850 h, the coating showed powdering and peeling; after 700℃ high temperature for 150 h, the coating showed powdering and peeling. At 650℃ high temperature, the surface temperature of the substrate decreased by 4.5±1℃; in the 9~12 μm frequency band, the 50℃ emissivity was <0.90; the 650℃ emissivity was <0.85.

[0068] Comparative Example 2 Comparing with Example 3, only Ta and V were removed, and the other parameters were the same as in Example 3.

[0069] The coating was sprayed, brushed or dipped on the surface of a 304 stainless steel surface which was subjected to surface sand blasting, and after curing at 120℃, a 80 μm protective coating was prepared.

[0070] The specific properties of the protective coating were as follows: After 1.7 x 10 5 After 1.7 x 10 After 600℃ high temperature for 800 h, the coating showed powdering and peeling; after 700℃ high temperature for 150 h, the coating showed powdering and peeling.

[0071] Comparative Example 3 Comparing with Example 3, only the acrylic modified silicone resin was changed to an epoxy resin, and the other parameters were the same as in Example 3.

[0072] The coating is applied to the surface of the 304 stainless steel treated by surface sand blasting by spraying, brushing or dipping, and an 80-micron protective coating is prepared after curing at 120℃.

[0073] The protective coating cannot be used at 600-700℃; the emissivity is ≤0.90 at 9-12-micron band at 50℃, and the coating cannot be used at 650℃.

[0074] Comparative Example 4 Compared with Example 3, only the amount of some components in the protective coating is changed, and the rest of the parameters are the same as those in Example 3. The components and amounts of the changed protective coating are as follows: 26 parts of acrylic-modified silicone resin, 1 part of Ta, 2 parts of V, 8 parts of copper-chromium black, 6 parts of iron-manganese black, 5 parts of B4C and 2 parts of Ta2O5, 12.5 parts of glass powder (consisting of 6 parts of SiO2-B2O3-Al2O3-CaF2-Na2O, 3.5 parts of SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2 and 3 parts of SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2), 8 parts of enamel (selected from the enamel micropowder in Example 1 in the patent with the application number CN201810069695.7), 11 parts of diluent (xylene), 0.1 part of leveling agent (BYK-354), 0.2 part of defoaming agent (BYK-052) and 0.2 part of wetting agent (Dow Chemical BD-405) The coating is applied to the surface of the 304 stainless steel treated by surface sand blasting by spraying, brushing or dipping, and an 80-micron protective coating is prepared after curing at 120℃.

[0075] The specific performance of the protective coating is as follows: After being irradiated by 1.7×10 5 Gy of gamma rays, the coating surface shows powdering and peeling phenomena; After being continuously subjected to high temperature at 600℃ for 700 h, the coating shows powdering and peeling phenomena; after being continuously subjected to high temperature at 700℃ for 140 h, the coating shows powdering and peeling phenomena.

[0076] It can be seen that the amount of each component in the protective coating is extremely important, and too much or too little amount of a single component will affect the overall performance of the protective coating.

[0077] Comparative Example 5 Compared with Example 4, only the “modified LDH nanosheet” is replaced with “zinc-aluminum-based LDH nanosheet modified by KH-792” (without doping Ce 3+ ); the components after the replacement and the amounts of the rest of the components are the same as those in Example 4. Preparation method: the rest of the preparation method is the same as example 3, except that the LDH nanosheet is zinc-aluminum-based and does not contain rare earth doping. Comparative example 6 Comparing example 4, replace the "KH-792 modified nanometer SiC particles" with "nanometer SiC particles" (i.e. unmodified), and replace the "KH-792 modified BN whisker" with "BN whisker" (i.e. unmodified); the component after replacement and the amount of the rest of the components are the same as example 3.

[0078] It is worth noting that all the parts mentioned in the examples and comparative examples are mass parts. Experimental example Sample preparation: multiple 304 stainless steel plates with a size of 50mm x 50mm x 2mm were selected as substrates, which were treated by sand blasting on the surface, and then coated with the paint (the paint of examples 1, 3-5 and comparative examples 5-6) by spraying, and cured at 120℃ for 2h to obtain a protective coating sample with a thickness of 80μm. Then the obtained sample was tested for related performance to verify whether the sample is suitable for primary circuit pipeline.

[0079] Before the following tests, the sample was subjected to γ-ray irradiation treatment: the sample was placed in a 350℃ environment, and subjected to γ-ray irradiation with a dose rate of 5Gy / h, and the cumulative dose reached 1.7x10 5 Gy, simulating the primary circuit radiation environment; after irradiation, the following performance tests were carried out.

[0080] Cracking resistance test: the sample was fixed in a high-pressure reaction kettle, and kept at 15MPa pressure and 350℃ for 24h, and then observed the number of cracks on the surface of the coating by optical microscope (100x magnification).

[0081] Steam permeation amount test: the sample was sealed in a permeation cup containing deionized water, and placed in a 350℃ saturated steam environment, and the mass change of the permeation cup was measured after 24h, and the steam permeation amount per hour per unit area (mg / cm²・h) was calculated.

[0082] Corrosion ion resistance test: the sample was immersed in simulated primary circuit water containing 5ppm Cl — (2ppm Fe 3+ and 1ppm Ni 2+ in addition to example 6), and kept at 350℃ and 10MPa for 72h, and the residual ion concentration in the solution was determined by inductively coupled plasma emission spectroscopy (ICP-OES), and the adsorption rate was calculated (adsorption rate = (initial ion concentration - residual concentration) / initial concentration x 100%).

[0083] The test results are shown in Table 1.

[0084] Table 1: Performance Index Example 1 Example 4 Example 5 Example 6 Comparative Example 5 Comparative Example 6 Resistance to cracking 1 streak No cracks No cracks No cracks 3 streaks of micro cracks 5 streaks of micro cracks Steam permeation 0.46 0.31 0.32 0.22 0.78 0.59 Resistance to corrosive ions 79% 92% 91% 97% (full ions) 64% 71% From Table 1, it can be seen that: In Example 1: The original coating lacks the mechanical strengthening of nano-SiC and BN whiskers, and is difficult to resist high pressure stress, and there is no barrier and adsorption effect of LDH nanosheets, resulting in relatively weak vapor permeation and ion adsorption performance, but still has strong protection ability for devices in space, nuclear radiation area or high temperature and high radiation environment.

[0085] In Examples 4-5: The mechanical properties are synergistically enhanced by nano-SiC and BN whiskers, resisting high pressure stress; the modified LDH nanosheets form a barrier layer and adsorb Cl — , improving the overall protection effect.

[0086] In Example 6: The introduction of EDTA disodium derivative between the LDH layers significantly improves the adsorption capacity of Fe 3+ , Ni 2+ , and further strengthens the barrier performance.

[0087] In Comparative Example 5: Zinc-aluminum-based LDH is used without rare earth doping, and three microcracks appear, the vapor permeation is 0.78 mg / cm²・h, the Cl — adsorption rate is 64%, the effect is poor, and it is difficult to achieve good protection effect. It shows that the layered structure of magnesium-aluminum-based LDH and Ce 3+ doping are crucial to maintaining high-temperature stability, barrier properties and ion adsorption capacity.

[0088] In Comparative Example 6: The unmodified nano-components have poor compatibility and are easy to agglomerate, resulting in a decrease in mechanical properties and ion adsorption capacity.

[0089] In summary, Examples 1-3 have excellent radiation resistance, high-temperature resistance and high-emissivity performance, and can protect devices in space, nuclear radiation area or high-temperature and high-radiation environment, and also have certain protection ability in primary circuit environment. Examples 3-5 introduce nano-silicon carbide particles modified by KH-792, modified LDH nanosheets and BN whiskers modified by KH-792, etc. on the basis of Example 1, through the synergistic effect of the new components and the components in Examples 1-3, the high-pressure cracking resistance, vapor barrier property and corrosion-resistant ion capacity of the coating are significantly improved, which can effectively adapt to the harsh environment of 300-400℃, 10-15MPa and γ-ray radiation in primary circuit pipeline, and achieve more comprehensive protection effect.

Claims

1. A radiation-resistant, high-temperature-resistant and high-emissivity protective coating, characterized in that: It comprises the following components in parts by weight: 20-30 parts of acrylic modified silicone resin, 15-20 parts of polyurethane resin, pigments and fillers, and 2-11 parts of enamel; The pigments and fillers include 1-3 parts of Ta, 1-3 parts of V, 5-8 parts of copper chrome black, 5-7.5 parts of iron manganese black, 10-13 parts of B4C and 1-3 parts of Ta2O5.

2. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 1, characterized in that: It comprises the following components in parts by weight: 22-28 parts of acrylic modified silicone resin, 16-19 parts of polyurethane resin, pigments and fillers, and 6-10 parts of enamel; The pigments and fillers include 1.2-2.5 parts of Ta, 1.2-2.5 parts of V, 5.5-7.5 parts of copper chrome black, 5.5-7 parts of iron manganese black, 10.5-12 parts of B4C and 1.5-2.8 parts of Ta2O5.

3. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 1, characterized in that: It comprises the following components in parts by weight: 26 parts of acrylic modified silicone resin, 18 parts of polyurethane resin, pigments and fillers, and 10 parts of enamel; The pigments and fillers include 2.2 parts of Ta, 2 parts of V, 6 parts of copper chrome black, 6 parts of iron manganese black, 12 parts of B4C and 2 parts of Ta2O5.

4. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 1, characterized in that: Also included are glass powders of various melting points.

5. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 4, characterized in that: The glass powder includes SiO2-B2O3-Al2O3-CaF2-R2O, SiO2-8B2O3-2.5Li2O-15Al2O3-3Na2O-15CaO-7CaF2 and SiO2-10Al2O3-6B2O3-6Na2O-6K2O-6SrO2; wherein R is Na or K.

6. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 5, characterized in that: The coating further comprises 0.3-1.2 parts of nano-silicon carbide particles modified with a silane coupling agent, 0.5-2 parts of modified double hydroxide nanosheets, and 0.2-0.8 parts of boron nitride whiskers modified with a silane coupling agent; The modified double hydroxide nanosheets are obtained by modifying magnesium aluminum double hydroxide with a silane coupling agent, and the magnesium aluminum double hydroxide is doped with Ce. 3+ or La 3+ .

7. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 1, characterized in that: It also includes one or more of a defoaming agent, a leveling agent and a dispersant.

8. The radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to claim 1, characterized in that: The coating thickness of the coating is 50-120 μm.

9. The method for preparing the radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to any one of claims 1 to 5, characterized in that: The acrylic modified silicone resin, pigments, fillers, enamel and diluent are mixed by ball milling, and after being evenly mixed, polyurethane resin is added and evenly dispersed to obtain the coating.

10. Use of the radiation-resistant, high-temperature-resistant and high-emissivity protective coating according to any one of claims 1 to 7 in a primary circuit.

Citation Information

Patent Citations

  • Antioxidant, corrosion-resistant, and impact-resistant high-temperature enamel coating and its preparation method

    CN108264232B

  • Graphene-based coating as well as preparation method and application thereof

    CN107033634A

  • Nuclear irradiation-resistant, corrosion-resistant and high-temperature-resistant multifunctional integrated organic silicon coating and preparation method thereof

    CN115160924A

  • Method for preparing Cys (at) MgAlCe-LDH / WPU self-repairing anti-corrosion coating

    CN117887343A

  • Jet fire impact-resistant insulating heat-insulating flame-retardant coating as well as preparation method and application thereof

    CN117987000A